INTERNATIONAL AIRPORT TAXIWAY RIGID PLANNING WITH PAVEMENT CLASSIFICATION NUMBER (PCN) - Andi Baso Gunawan; Mohammad Junaedy Rahman (Moeslim Indonesian University (UMI), 2020)
Pavement Classification Number (PCN) which has been determined as a requirement in the planning of airport pavement thickness by the Director General of Civil Aviation, Ministry of Transportation Directorate General of Air Transportation in 2015. The airport apron pavement design uses rigid pavement for Boeing 747 series 400 (B747 - 400). The planned pavement layers consist of a surface layer in the form of a concrete slab, and a subbase layer under the concrete layer. The quality of the rigid pavement design concrete is K-400 or fck' 40 MPa. In this study, the calculation results obtained that the total thickness of the rigid pavement layer was 560 mm consisting of the Surface Course PCC layer thickness which was rounded to 400 mm and the thickness of the P-306 Econocrete Subbase layer. which is rounded off to 160 mm. The need for longitudinal and transverse reinforcement in the Surface Course PCC layer uses wire mesh type M8 or D8-150. The requirement for the minimum ratio of FAA slab reinforcement is 0.6%. The use of 22 mm diameter plain iron with a distance of 200 mm (P22-200) for dowel reinforcement resulted in a reinforcement area of ​​Asd = 1900 mm2 per meter which was greater than the dowel requirement required by the FAA.